Aktionsart, aspect and category change in the history of Greek - Amalia Moser (K. Bentein, M. Janse & J. Soltic (eds.) Variation and Change in Ancient Greek Tense, Aspect and Modality, 2017)
Aspect is more or less universally recognized as the defining TMA category of the Greek verbal system. There is a consensus on this in both the philological tradition and the linguistic literature on aspect. It is moreover almost universally accepted that diachronically the Greek verbal system has been extremely conservative, remaining practically unchanged down to the present day. This paper largely accepts the former assumption, but not the latter, which has been increasingly challenged in the last few years. It is argued here that, while there has been little change morphologically, the system has been altered in a fundamental way. More specifically, it takes up the analysis proposed in Moser (2008 and 2009), according to which the history of the Greek verb indicates that the system of three (and later two) stems shifts from the expression of Aktionsart (actionality/lexical aspect) to the expression of (grammatical) aspect, and develops it further, taking a fresh look at the data from a different point of view and in the light of recent studies.